Studies on Character Association and Path Analysis for Yield and its Contributing Traits in Chickpea [Cicer arietinum (L.)] - Chopdar, D. K.; Bharti, Baudh; Sharma, P. P.; Khatik, C. L.; Vyas, Mukesh (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at the Experimental Farm, Department of Plant Breeding and Genetics, Rajasthan College of Agriculture, MPUAT, Udaipur, during rabi season 2012−13, in randomized block design with three replications. The experimental material comprised of 20 genotypes. Each genotype was sown in four rows of 4 m length and 1.20 m width with spacing of 30 cm between the rows and 10 cm between the plants within rows. At both genotypic and phenotypic level plant height was exhibited highly significant and positive correlation with days to maturity. However, it was exhibited non- significant and negative correlation with days to 50% flowering at both genotypic and phenotypic level. Days to maturity exhibited non-significant and positive association with days to 50% flowering at both genotypic and phenotypic level. Seed yield plant-1 showed significantly and positive correlation with harvest index, number of seeds pod-1, primary branches plant-1, number of pods plant-1, biomass plant-1, and 100-seed weight indicating that an intense selection for these characters will improve seed yield in chickpea. Path coefficient analysis revealed that day to maturity, primary branches plant-1, biomass plant-1, harvest index protein content and number of seeds pod-1 were major characters influencing seed yield directly and indirectly. The component of residual effects of path analysis was low residual effect indicated that characters for path analysis were adequate and appropriate. The results indicated that number of seeds pod-1 is responsible for manipulation of seed yield in chickpea.